2018
DOI: 10.1142/s0217979218500911
|View full text |Cite
|
Sign up to set email alerts
|

A model to study finite-size and magnetic effects on the phase transition of a fermion interacting system

Abstract: We present a model to study effects from an external magnetic field, chemical potential, and finite size, on the phase structure of a massive four-and six-fermion interacting system. These effects are introduced by a method of compactification of coordinates, a generalization of the standard Matsubara prescription. Through the compactification of the z coordinate and of imaginary time, we describe a heated system with the shape of a film of thickness L, at temperature β −1 undergoing first-or second-order phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In the finite size context, we have found that the magnetic field produces the direct and inverse catalysis effects in the Gross-Neveu model in the Refs. [24,25] and [24,26], respectively. In the Nambu-Jona-Lasinio model, the IMC phenomenon at finite size was found in [27] and the MC considering finite size of the system was found in [4,28].…”
Section: Introductionmentioning
confidence: 99%
“…In the finite size context, we have found that the magnetic field produces the direct and inverse catalysis effects in the Gross-Neveu model in the Refs. [24,25] and [24,26], respectively. In the Nambu-Jona-Lasinio model, the IMC phenomenon at finite size was found in [27] and the MC considering finite size of the system was found in [4,28].…”
Section: Introductionmentioning
confidence: 99%